Glaukoma sekunder pada pasien anak dengan Sindrom Sturge Weber: laporan kasus - Putu Dian Megasafitri; I Gusti Ayu Ratna Suryaningrum; I Made Agus Kusumadjaja (DiscoverSys Inc., 2021)
Background: Sturge Weber's Syndrome (SSW) is a rare congenital disorder characterized by hemangiomas found in several parts of the body, such as the ocular, intracranial, and facial skin structures. Patients with SSW often experience glaucoma as one of the frequent ocular manifestations which can occur from birth or throughout life and can cause blindness. This case report aims to report the management of a pediatric patient with SSW who underwent trabeculectomy after failing to maintain intraocular pressure with topical drugs.Case Presentation: A 5-year-old girl had increased intraocular pressure and optic nerve glaucoma signs in her right eye. This patient also had a birthmark in the form of a port-wine stain on her face's right side. After undergoing several tests, the patient was diagnosed with secondary glaucoma due to SSW with poor intraocular pressure control after 1.5 years of topical selective beta-blocker treatment. Trabeculectomy + 5-fluorouracil (5-FU) is performed to reduce intraocular pressure and prevent worsening of glaucoma. On the first day after surgery, the intraocular pressure was 20 mmHg in the right eye and decreased significantly during follow-up.Conclusion: Trabeculectomy is one of the treatment options to treat glaucoma in SSW patients, which results in reasonable control of intraocular pressure. Latar Belakang: Sindrom Sturge Weber (SSW) adalah kelainan bawaan yang jarang terjadi dimana ditandai dengan adanya hemangioma yang terdapat pada beberapa bagian tubuh, seperti struktur kulit okuler, intrakranial, dan wajah. Pasien dengan SSW sering mengalami glaukoma sebagai salah satu manifestasi okuler yang sering terjadi dimana dapat muncul sejak lahir maupun sepanjang masa kehidupannya serta dapat menyebabkan kebutaan. Laporan kasus ini bertujuan untuk melaporkan penatalaksanaan pada pasien anak dengan SSW yang menjalani prosedur trabekulektomi setelah gagal mempertahankan tekanan intraokuler dengan obat topikal.Presentasi Kasus: Seorang anak perempuan berusia 5 tahun mengalami peningkatan tekanan intraokuler dan tanda-tanda saraf optik glaukoma di mata kanannya. Pasien ini juga memiliki tanda lahir berupa port wine stain di bagian kanan wajahnya. Setelah menjalani beberapa pemeriksaan, pasien terdiagnosa menderita glaukoma sekunder oleh karena SSW dengan kontrol tekanan intraokuler yang buruk setelah 1,5 tahun menjalani pengobatan topikal golongan beta bloker selektif. Operasi trabekulektomi + 5-fluorouracil (5-FU)dilakukan untuk menurunkan tekanan intraokuler dan mencegah perburukan glaukoma. Pada hari pertama setelah operasi, tekanan intraokuler menjadi 20 mmHg pada mata kanan dan berkurang secara bermakna selama masa tindak lanjut.Kesimpulan: Trabekulektomi merupakan salah satu pengobatan pilihan untuk mengobati glaukoma pada pasien SSW yang menghasilkan kontrol tekanan intraokuler yang baik.